Educação popular e economia solidária: o caminho da Rede Mandala para formação de educadores populares - Correa, Gabriela Fernanda Rocha (2024)
Popular Education, grounded on Freirean principles, promotes awareness and emancipation of individuals, seeking to strengthen popular groups through collective and participatory education. This educational approach, when allied with the Solidarity Economy, reinforces practices of self-management and cooperation, essential for building a just society by valuing the work and participation of workers in productive processes. Solidarity Technoscience refers to the Social Technology movement in conjunction with the principles and pillars of the Solidarity Economy and other social and labor movements, promoting the development and application of knowledge in a supportive and inclusive manner. Solidarity Technoscience in the practice of Popular Education and the Solidarity Economy means going beyond the mere transfer of technology. It is a dialogic and collaborative process, where knowledge is democratized. The general objective of this research was to understand how ongoing training, through Popular Education, can contribute to the strengthening of the Solidarity Economy in the Mandala Network. The specific objectives were: To investigate the current context of Popular Education and the Solidarity Economy, identifying the trends, challenges and opportunities that affect the training of popular educators in the context of the Mandala Network; To describe the process of Permanent Training in Solidarity Economy of the Mandala Network, considering the pedagogical methods, content and strategies used; To analyze the perceptions of popular educators about their participation in the Permanent Training in Solidarity Economy of the Mandala Network; and To verify whether the Permanent Training in Solidarity Economy of the Mandala Network can be considered a Solidarity Technoscience. This study used a qualitative and descriptive approach to explore the permanent training in Solidarity Economy in the Mandala Network. To this end, a bibliographical survey and documentary research were carried out, in addition to nine semi-structured interviews with popular educators. Content Analysis was used to treat the data, allowing a detailed and contextualized interpretation of the results obtained. The categories of analysis found were: collective construction; ongoing training; a training, a process, and the experience of each educator. The research emerged from a reflection on our society, governed by capital and consumption, patterns also reflected in educational structures. Through Freirean Popular Education, it is possible to strengthen the Solidarity Economy. In this sense, the Permanent Training in Solidarity Economy of the Mandala Network can be considered a practical example of the implementation of Freirean Popular Education as a solidary Technoscience within the Solidarity Economy. Popular Education, combined with the Solidarity Economy and Solidarity Technoscience, offers a viable path for the construction of a just society, where the protagonism of popular groups is valued and encouraged.